Mount Sinai expert guides. Gastroenterology - Sands, Bruce E. (Chichester, West Sussex, UK : John Wiley and Sons, 2014)
Mount Sinai Expert Guides: Gastroenterology will provide physicians with an extremely clinical and accessible handbook covering the major GI diseases and symptoms, their diagnosis and clinical management. Perfect as a point-of-care resource on the hospital wards and also as a refresher for board exam preparation, the focus throughout is on providing rapid reference, essential information on each disease to allow for quick, easy browsing and assimilation of the must-know information. All chapters follow a consistent template including the following features: - An opening bottom-line/key points section - Classification, pathogenesis and prevention of disease - Evidence-based diagnosis, including relevant algorithms, laboratory and imaging tests, and potential pitfalls when diagnosing a patient - Disease management including commonly used medications with dosages, when to perform surgery, management algorithms and how to prevent complications - How to manage special populations, ie, in pregnancy, children and the elderly - The very latest evidence-based results, major society guidelines (ASG/ACG/UEGW) and key external sources to consult In addition, the book comes with a companion website housing extra features such as case studies with related questions for self-assessment, key patient advice and ICD codes. Each guide also has its own mobile app available for purchase, allowing you rapid access to the key features wherever you may be. If you specialise in gastroenterology and require a concise, practical guide to the clinical management of GI disease, bought to you by one of world's leading hospitals, then this is the perfect book for you.
Section 5: Special PopulationsSection 6: Prognosis; Section 7: Reading List; Suggested Websites; Section 8: Guidelines; Section 9: Evidence; Section 10: Images; CHAPTER 9: Approach to the Pregnant Patient with GI Disorders; Section 1: Background; Section 2: Prevention; Section 3: Diagnosis; Section 4: Treatment; Section 5: Special Populations; Section 6: Prognosis; Section 7: Reading List; Suggested Websites; Section 8: Guidelines; Section 9: Evidence; Section 10: Images; PART 2: Specific Diseases/Conditions; CHAPTER 10: Gastroesophageal Reflux Disease; Section 1: Background.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Gastrointestinal diseases; Gastroenterology; Gastrointestinal system -- Diseases; Medical; Electronic books